LATIN BORROWINGS IN ENGLISH AND UKRAINIAN - Остапенко, Світлана; Удовіченко, Ганна; Герасименко, Ольга (Modern engineering and innovative technologies, 2024)
The article deals with the borrowings of Latin origin in the English and Ukrainian languages. The authors analyze examples of adaptation of Latin borrowings in various spheres of life. The focus is also on four types of lexical units, taking into account